Utilization of “Skim Peduli Kesihatan untuk Kumpulan B40” (PeKa B40) Programme among Felda Residence in Kedah, Malaysia: The Participation Rate and its Determinants - Isa, Mohamad Rodi; Mohd Zuki, Abdul Hadi; Suddin, Leny Suzana (IIUM Medical Journal Malaysia, 2026)
INTRODUCTION: The Malaysian government has implemented the “Skim Peduli Kesihatan untuk Kumpulan B40” (PeKa B40) programme in response to the growing rate of non-communicable diseases (NCD) among the Malaysian population. This study aims to determine the participation rate of PeKa B40 programme utilization and its determinants. MATERIALS AND METHODS: This was a cross-sectional study designed at Felda Lubuk Merbau Kedah. A total of 237 participants were involved using the simple random sampling method from January-April 2023. Multiple logistic regression analysis was used to determine the determinants. RESULTS: The participation rate of PeKa B40 utilization among participants was 41.8%. The determinants of utilization of PeKa B40 programme were positively associated with age [Adj. OR: 1.06 (95%CI: 1.03, 1.10)], female gender [Adj. OR: 2.32 (95%CI: 1.15, 4.66)], presence of chronic disease [Adj. OR: 2.62 (95%CI: 1.28, 5.37)], persistent pain that mildly disturbs daily activities [Adj. OR: 3.30 (95%CI: 1.31, 8.33)], and high disturb daily activities [Adj. OR: 14.34 (95%CI: 2.18, 94.26)]. The determinants were also negatively associated with poor self-rate health [Adj. OR: 0.05 (95%CI: 0.01, 0.47)], intermediate self-rate [Adj. OR: 0.25 (95%CI: 0.06, 0.95)], and good self-rate [Adj. OR: 0.22 (95%CI: 0.06, 0.82)]. CONCLUSION: The participation rate of PeKa B40 among residents of Felda Lubuk Merbau was higher than at the national and state levels. Therefore, the government needs to advertise this programme and take more proactive steps to advertise the programme especially, to adult men. This programme needs to be extended to those respondents who are sick and need medical treatment.